TRADISI TIBAN DI KECAMATAN TRENGGALEK DALAM PERSPEKTIF FIQH - Ihtiar, Habib Wahidatul (Ahkam: Jurnal Hukum Islam, 2016)
This study was conducted concerning the real condition in the society indicating that people in Trenggalek still do Tiban ritual, which is not prescribed by Fiqh, to expect the coming of the rain after a long dry season, in contrast to asking for the rain to Allah SWT. The focuses of this study are (1) why do the people in Trenggalek district still conduct Tiban ritual? (2) How do people in Trenggalek district practice Tiban ritual? (3) How is Fiqh perspective towards Tiban ritual in Trenggalek district? This study was qualitative research employing field research design. To obtain valid and accurate data, the data collecting methods were (1) Determining informants, (2) Observation, and (3) Deep interview. The data were then analyzed by using interactive method. The results of this study were as the following; (1) There were three reasons why the people in Trenggalek district do Tiban tradition. The first is due to a long dry season. The second is the believe of people that Tiban tradition is the quicker way to ask for the rain, and the last is that Tiban tradition is highly expected as a media to perpetuate the ancient culture; (2) The practice of Tiban tradition consists of three steps: opening step, action step, and closing step; (3) From Fiqh perspective, it can be said that Tiban is such a forbidden tradition. Kata kunci: Tradisi Tiban, Fiqh